LEARNING THE CRITICAL POINTS FOR ADDITION IN MATEMATIKA GASING - Johannes Hamonangan Siregar; Wiwik Wiyanti; Nur Safitri Wakhyuningsih; Ali Godjali (Journal on Mathematics Education, 2014)
We propose learning Matematika GASING to help students better understand the additionÂ material. Matematika GASING is a way of learning mathematics in an easy, fun and enjoyableÂ fashion. GASING is short for GAmpang, aSyIk, and menyenaNGkan (Bahasa Indonesia forÂ easy, fun and enjoyable). It was originally developed by Prof. Yohanes Surya at the SuryaÂ Institute in Indonesia to improve the mathematics education in Indonesia. In MatematikaÂ GASING, there is a step called â€œthe critical pointâ€ that needs to be mastered for eachÂ topic. The focus of our research is the critical point for addition, that is addition of twoÂ numbers between 1 âˆ’ 10 with a sum less than 20. The subject is a matriculation class atÂ STKIP Surya and the research method used is Classroom Action Research. The statisticsÂ obtained is described using Qualitative Descriptive Statistics.Keyword: Matematika GASING, Addition, Critical Points, Classroom Action Research.Â DOI: http://dx.doi.org/10.22342/jme.5.2.1500.160-169